Bone mineral density, body composition and metabolic profiles in adult women with complete androgen insensitivity syndrome and removed gonads using oral or transdermal estrogens. Issue 6 (December 2019) - Gava, Giulia; Mancini, Ilaria; Orsili, Isabella; Bertelloni, Silvano; Alvisi, Stefania; Seracchioli, Renato; Meriggiola, Maria Cristina
Abstract : Objectives: To assess bone health in adult women with complete androgen insensitivity syndrome (CAIS) and removed gonads compared with age-matched healthy controls. To evaluate the effects of transdermal oestradiol 2 mg or oral estradiol valerate 2 mg on bone, biochemical and clinical characteristics. Design: Cohort study. Methods: Bone, body composition and anthropometric parameters were assessed in 32 adult CAIS and 32 healthy controls. In 28 cases, CAIS evaluations of metabolic, bone and body composition were performed also after a maximum of 6 years of therapy. Results: Lumbar, femoral and total body bone mineral density (BMD) were significantly lower in those with CAIS when compared with controls. The prevalence of vertebral osteoporosis and osteopenia was significantly higher in the CAIS group ( P  = 0.038, OR = 9.67, 95% CI: 1.13–82.83 and P  = 0.012, OR= 3.85, 95% CI: 1.34–11.16, respectively). Prevalence of femoral osteopenia was significantly higher in the CAIS group ( P  = 0.0012, OR = 7.93, 95% CI: 2.26–27.9). During follow-up, lumbar BMD significantly increased suggesting a significant effect of treatment on BMD ( P  = 0.0016), while femoral and total body BMD did not show any significant change. Total body BMD values were positively associated to the duration and route of oestrogen administration and to serum estradiol levels. Transdermal administration of estrogens was associated with better total body BMD in comparison to oral administration. Conclusions: Our results reinforce the importance of adequate hormonal treatment for women living with CAIS, suggesting a better effect from the transdermal route over the oral route.